ISTRI KARIR PRESPEKTIF KESETARAAN GENDER DAN HUKUM ISLAM - Siti Sa’adatul Kutsiyah; Ach. Faisol; Khoirul Asfiyak (Jurnal Hikmatina, 2019)
Wives who work outside the home will have a negative impact such as there is no harmony in the household, neglect of all household affairs, and seen from the gender side of the wife who is a woman considered inappropriate for work and career because it is considered to overtake nature. This type of research is a library reseach, the research method used is analysis using normative and syar'I approaches where the normative approach itself is defined as things that follow certain rules or norms and syar'i are the rules contained in the law Islam. This is what can be used as a reference for how religious norms look at wives who have careers. He idea of gender equality has been used to discriminate women. Some theorists believe that the solution is not to replace differences with similarities but to recognize important differences that exist in a woman and a man. in Islam itself the prohibition of a woman working or having a career does not exist as long as they do not deny her nature to keep running her reproductive system as a woman.Kata Kunci: Career wife, gender equality, Islamic law.